Pathways Involved in the Development of Vasculogenic Mimicry in Canine Mammary Carcinoma Cell Cultures. (April 2022) - Guiraldelli, Giulia G.; Prado, Maria Carolina M.; de F Lainetti, Patrícia; Leis-Filho, Antonio F.; Kobayashi, Priscila E.; Cury, Sarah S.; Fonseca-Alves, Carlos E.; Laufer-Amorim, Renee
Summary: Vasculogenic mimicry (VM) is the ability of highly aggressive cancer cells to form fluid-conducting channels that facilitate the nutrition and metastasis of cancer cells. Considering the importance of VM in the prognosis of canine mammary gland tumours, this study aimed to investigate global gene expression in two canine mammary carcinoma cell cultures associated with the capacity for VM in vitro . The cell lines were subjected to an in-vitro assay to form VM channels (3D culture). Each cell line was then used in 2D conditions as controls and we compared the global gene expression with that of the 3D cultures. A total of 1, 217 differentially expressed genes (DEGs) ( P <0.05, fold change >2.0 or <2.0) were observed in 3D conditions compared with 2D culture in the UNESP-CM9 cell line, of which 677 were upregulated genes and 540 were downregulated. In contrast, the UNESP-CM60 cell line had only one upregulated and two downregulated genes. Overall, we identified several genes and pathways involved in the development of VM and these molecular data will be useful for future studies aimed at identifying diagnostic and therapeutic targets for VM in canine mammary carcinoma.